Solution algorithms for single-machine group scheduling with ready times and deteriorating jobs. Issue 5 (4th May 2019) - Liu, Feng; Yang, Jing; Lu, Yuan-Yuan
ABSTRACT: This article considers the single-machine group scheduling problem with deterioration effect and ready times. The objective of this problem is to determine the sequence of groups and the sequence of jobs to minimize the makespan. To solve the problem, an algorithm based on enumeration, an heuristic algorithm and a branch-and-bound algorithm are developed and exhaustively tested. The computational results show that the performance of the heuristic algorithm is fairly accurate in obtaining near-optimal solutions and the branch-and-bound algorithm is very effective in obtaining optimal solutions.